Selected individual and environmental factors predisposing to Human papillomavirus infections. Part II. Genital HPV infection - Samochocki, Zbigniew; Rujna, Paweł; Malejczyk, Magdalena; Majewski, Sławomir (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Infections with genital types of HPV, particularly those with high oncogenic potential constitute a significant epidemiological problem. Most studies have been performed in women due to the risk of cervical cancer development. Reports concerning men are less frequent, although men are the main source of infection. Objective. Assessment of the incidence of symptomatic and asymptomatic infections with genital types of HPV in young men and determination of factors predisposing to their development. Material and methods. The study involved 340 healthy men aged 19-26 years. Clinical and viral examinations were performed twice with a six-month interval. The infection with oncogenic HPV types was studied using a PCR test. Results. Genital warts were found in 2.5% and asymptomatic infection with oncogenic HPV types was diagnosed in 20.6% of cases on the first visit and in 16.8% on the second. During six-month follow-up results of the PCR test in 18/23 cases became negative and in 5/23 cases they remained positive. Genital warts and oncogenic HPV infection were statistically significantly more frequently observed in men with coexistent common warts, atopic dermatitis, skin dryness and pruritus, herpes simplex virus infection, in persons reporting casual sexual contacts and not using condoms, and those attending swimming pools and solaria. Conclusions. Infection with oncogenic types of genital HPV constitutes a greater epidemiological risk than condylomata acuminata and the course of infection is more dynamic. Spreading of these infections is significantly influenced not only by environmental factors and sexual behaviour, but also by individual predispositions, particularly such as coexistent atopic dermatitis, skin dryness and pruritus. The occurrence of common warts should suggest performance of periodic tests in order to exclude infection with potentially oncogenic genital HPV types.